Learning Chinese through stories and activities - Louie, Belinda Yun-Ying (Book Publishers Network, 2007)
"...The Chinese/English bilingual texts allow both novice and advanced Chinese language learners to sharpen their language skills while enjoying the stories..."--Cover back